Lee Kuan Yew and Suharto : how mutual trust fostered bilateral ties - Desker, Barry (2015)
The excellent relations between Indonesia and Singapore from the 1970s were fostered by the mutual trust that developed between President Suharto and Prime Minister Lee Kuan Yew.